Mapping policymaker narratives of the climate security nexus on social media: A case study from Kenya - Silveira Carneiro, Bia; Resce, Giuliano; Ruscica, Giosuè (Universitat Politècnica de València, 2023)
Despite increasing awareness of the nexus between climate change and human security, especially in fragile contexts, this complex relationship has yet to be reflected in the policy arena. To investigate this potential policy gap, we apply an online issue mapping approach to assess representations of climate security within the public discourse of policymakers on social media, using Kenya as a case study. Considering Twitter as a proxy for public debate, text mining and network analysis techniques were employed to a corpus of almost 50 thousand tweets from selected national-level state actors, aiming to identify the evolution of thematic trends and actor dynamics. Results show a disassociation between climate, socioeconomic insecurities, and conflict in the public communications of national policymakers. These findings can have useful implications for the policy cycle, indicating where policy attention around climate security-related topics has been and what are the entry points for enhancing sensitivity on the issue.